L’éducation à la majorité selon Theodor W. Adorno - Alain-Patrick Olivier (Éducation et Socialisation)
What is the actual state, in our democratic societies, of the education of the citizen towards citizenship? This paper will focus on the idea of an education to majority. The critical enquiry made by Theodor W. Adorno after World War II as sociologist and philosopher led him to the conclusion that not only is this process of critical and democratic education not really carried out but also the mere willingness to carry out such education remains to be evidenced. On the contrary, Adorno points out a number of processes that seem to run counter to this aim, or indeed that are putting into place precisely the conditions making such an education for autonomy impossible. In this paper, I will discuss three problematic concepts taken from Adorno’s philosophy, which appear to have potential for an update in this respect, namely Aufklärung, the culture industry and authoritarian personality. I will focus on an interview with the German philosopher, as of yet unpublished in French, entitled “Erziehung zur Mündigkeit” (Education for Autonomy).